2008
DOI: 10.1080/13691050801999071
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal practices: eroticism and implications for women's health and condom use in Mozambique

Abstract: This paper analyses two female sexual practices in Tete Province, Mozambique: (1) the practice of elongating the labia minora and (2) what is sometimes called 'dry sex' involving the insertion of natural and/or synthetic products into the vagina or the ingestion of these products orally. These practices are fundamental to the construction of female identity, eroticism and the experience of pleasure. Notions such as 'closed/open', 'dry/damp', 'hot/cold', 'heavy/light', 'life/death', 'wealth/poverty' and 'sweet/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
73
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 12 publications
1
73
2
Order By: Relevance
“…(FGD with rural men age [19][20][21][22][23][24][25][26][27][28][29][30] "…If the umuthi is on me then I don't see that.…”
Section: Men's Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…(FGD with rural men age [19][20][21][22][23][24][25][26][27][28][29][30] "…If the umuthi is on me then I don't see that.…”
Section: Men's Perspectivesmentioning
confidence: 99%
“…You see, girls are witches." (FGD with rural men age [18][19][20][21][22] Almost all women in the survey reported nondisclosure of genital incisions (94.4%). When asked what their partner would do if he found out, 37.7% said he would be angry while 32.3% believed discovery would result in violence or abandonment.…”
Section: Men's Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, sexual pleasure was found to be studied while investigating different sex practices especially among women. For example, Bagnol et al reported on two sex practices among Mozambiquan women-elongation of the labio minora and insertion of natural or synthetic products into the vagina (dry sex) 37 . These practices were usually undertaken for female identity and enhancement of sexual pleasure.…”
Section: Pleasure Pressure and Painmentioning
confidence: 99%
“…One practice that has been widely described amongst women in African countries such as Uganda and Zimbabwe is the stretching of the labia, a practice which represents a woman's initiation into sexuality (Bagnol & Mariano, 2008a, 2008bTamale 2005;Williams, 1969). In a study carried out among Shona women in Zimbabwe it was noted during medical observations that most of the women possessed elongated labia (Williams, 1969).…”
Section: Traditional Practices Of Enhancing Eroticismmentioning
confidence: 99%